Organised labour : - Cole, G. D. H. (G. Allen and Unwin Ltd, the Labour Pub. Co, 1924)
Contents: the structure of trade Unionism; The government of trade Unionism; Internal trade Union problems; Trade Unions at work; trade Unionism and the states;...